Survey Engine Management System - Ismail, Nurul Hayati (universiti teknologi petronas, 2005)
In today's highly competitive marketplace, business owners are continuously forced to act quickly in order to increase profits, create effective customer acquisition programs, and reduce customer defection. Web-based surveys continue to take on a strategic and instrumental role in the customer life cycle as they enable companies to gain valuable feedback, and hear the "voice" of the customer. The overall objective of the study is to identify whythe issues of online surveys currently provided in Malaysia and to recognize important features to be considered at the implementation phase to enable successful implementation of a sound survey engine. Previous research efforts show that although plenty of survey engine have beendeveloped, much effort and research is still needed to ensure proper feedback and higher response rate from the targeted audience. It is hoped that all the necessary information will be collected through the use of surveys, journals, previous researches and interviews. At the end of this study, a thorough and detailed survey engine will be created. It is hoped that this study will be able to achieve its objectives and make important contributions to the improvement of the creations of online surveys; particularly to the e-business sector in Malaysia. 111